Uveítis y glaucoma asociados a infección por Hepatozoon canis: reporte de un caso - Acevedo, Sandra P.; Ramírez, Mauricio; Restrepo R., Luis G. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary This paper is about the clinical case of a five in a half years old German Sheeper, which presented anterior uveitis in his left eye that later became into galucoma and corneal ulcers. The clinic exam performed to the dog showed a patient with low corporal condition, muscular weekeness, accompanied by dull and fragile hair, which are associated symptoms of hepatozoonosis. In the studies performed to the dog It was found gamonts of Hepatozoon canis in blood and aqueous humor. Diagnosis, treatment and progress are reported.